Pulse recruitment and recovery of Cayman Islands Nassau Grouper (Epinephelus striatus) spawning aggregations revealed by in situ length-frequency data. (8th January 2021) - Stock, Brian C; Heppell, Scott A; Waterhouse, Lynn; Dove, India C; Pattengill-Semmens, Christy V; McCoy, Croy M; Bush, Phillippe G; Ebanks-Petrie, Gina; Semmens, Brice X
Abstract: Fish spawning aggregations (FSAs) are vulnerable to overexploitation, yet quantitative assessments of FSA populations are rare. We document an approach for how to conduct such an assessment, evaluating the response of Critically Endangered Nassau Grouper ( Epinephelus striatus ) to protections in the Cayman Islands. We assessed pre-protection status on all islands using length data from fishery catch. We then used 17 years of noninvasive length-frequency data, collected via diver-operated laser calipers, to estimate recruitment and spawning biomass of Nassau Grouper on Little Cayman following protection. Bimodal length distributions in 2017–2019 indicated a large recruitment pulse (4–8× average) derived from spawning in 2011. Biomass recovered to 90–106% of the pre-exploitation level after 16 years, largely driven by the strong 2011 year class. Length distributions were also bimodal in 2017–2019 on nearby Cayman Brac, implying a synchronous recruitment pulse occurred on both islands. Our results demonstrate that: (i) in situ length data can be used to monitor protected FSAs; (ii) spatiotemporal FSA closures can be effective, but success takes time if population recovery depends upon sporadic recruitment; and (iii) FSA fishery management targets may need to be higher than commonly recommended (i.e. spawning potential ratio >0.6 instead of 0.4).